Nature Brings Happiness: Contact with Nature as Mediator Between Nature Relatedness and Well-being Among Urban Communities in Indonesia - Adiwena, Bartolomeus Yofana; Djuwita, Ratna (UI Scholars Hub, 2024)
Well-being is one of the most important elements and is known to be closely related to various aspects of human life, such as physiological health. Previous studies demonstrate that the natural environment positively contributes to well-being. However, most research on the natural environment and well-being mainly focuses on situational factors, such as contact with the natural environment, and ignores dispositional factors, such as nature relatedness. Thus, the current study aims to examine the role of nature relatedness (dispositional factor) and contact with nature (situational factor) in improving well-being among urban communities in Indonesia. This study uses a cross-sectional design and recruits 596 adults from various urban areas in Indonesia. Data were analyzed using structural equation modeling. The results indicate that the level of nature relatedness positively predicts well-being, while contact with nature partially mediates this relationship. Individuals with high levels of nature relatedness tend to make contact with the natural environment. This contact with nature ultimately predicts an increase in well-being. Thus, the study proves the mechanism that underlies the relationship between nature relatedness and well-being and illustrates that situational and dispositional factors play an essential role in well-being among urban societies.